RELATIONS BETWEEN THE UIGHURS AND TANG CHINA, 744-840 - Colin MACKERRAS (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
This article focuses on the relations between the Uighur state of the period 744 to 840 and China under the Tang dynasty and their mutual impact. The article covers four aspects of the relationship: the military, diplomatic, economic, as well as alliances through marriage.1 Although the influence was mutual, that from China on the Uighur state was greater than the other way around. This was hardly surprising given the imbalance between the size of the populations and age of the cultures. Moreover, not all this influence from China was specifically Chinese, since a major element was in the form of Manicheism, which is Persian in origin and not a religion the Chinese liked.